Faktor-faktor yang mempengaruhi pemberian ASI eksklusif di wilayah kerja Puskesmas Batujaya Karawang - Susilawati, Susi; Mayasari, Dyah (Holistik Jurnal Kesehatan, 2024)
Background: Increasing breast milk production needs to be done to increase the success of breastfeeding babies in an effort to improve the health of babies and mothers. Based on the 2021 Indonesian National Health Profile, the coverage of babies receiving exclusive breastfeeding in 2021 was 56.9%, a decrease compared to the previous year, namely 66.1%. Several causes related to breast milk production include knowledge, employment, early initiation of breastfeeding, husband's support, and early marriage. Purpose: To determine the factors that influence exclusive breastfeeding. Method: Quantitative analytical research with cross sectional design. The research sample consisted of 108 mothers who had babies aged 7-12 months using the Accidental Sampling technique. The research instrument used a questionnaire, primary data was analyzed using the chi square test. Results: Most breastfeeding mothers had poor knowledge as much as 63.0%, worked 50.9%, did not practice early initiation of breastfeeding 58.3%, husbands did not support 57.4%, did not have early marriages 68.5%, and gave exclusive breastfeeding 57.4%. The results of bivariate analysis show that there is a relationship between knowledge (p-value=0.028), employment (p-value=0.000), implementation of early breastfeeding initiation (p-value=0.004), husband's support (p-value= 0.007), and early marriage (p-value=0.012) with exclusive breastfeeding. Conclusions: Knowledge, occupation, implementation of early breastfeeding initiation, husband support, and early marriage are associated with exclusive breastfeeding. Suggestions: Hoped that midwives can help breastfeeding mothers about the impact of early marriage, the importance of breastfeeding and information about the importance of husband support for mothers so that husbands understand and know about it through counseling and counseling and using advertisements or posters.   Keywords: Early Breastfeeding Initiation; Early Marriage; Employment; Exclusive Breastfeeding; Husband Support; Knowledge.   Pendahuluan: Peningkatan produksi ASI perlu dilakukan untuk mendukung keberhasilan menyusui bayi dalam upaya meningkatkan kesehatan bagi bayi dan ibu. Menurut Profil Kesehatan Indonesia tahun 2021 secara nasional, cakupan bayi mendapat ASI eksklusif sebesar 56.9%, mengalami penurunan jika dibandingkan dengan tahun sebelumnya yaitu mencapai 66.1%. Beberapa penyebab yang berhubungan dengan produksi ASI antara lain, pengetahuan, pekerjaan, pelaksanaan inisiasi menyusu dini (IMD), dukungan suami, dan pernikahan dini. Tujuan: Untuk mengetahui faktor-faktor yang memengaruhi pemberian ASI eksklusif. Metode: Penelitian analitik kuantitatif dengan rancangan cross sectional. Sampel penelitian yaitu ibu mempunyai bayi berumur 7-12 bulan sebanyak 108 responden dengan teknik accidental sampling. Instrumen penelitian menggunakan kuesioner dan data dianalisis menggunakan univariat dan bivariat uji  chi square. Hasil: Sebagian besar ibu menyusui dengan pengetahuan kurang baik 63.0%, bekerja 50.9%, tidak melakukan IMD 58.3%, suami tidak mendukung 57.4%, tidak melakukan pernikahan dini 68.5%, dan pemberian ASI eksklusif 57.4%. Terdapat hubungan antara pengetahuan (p-value=0.028), pekerjaan (p-value=0.000), pelaksanaan inisiasi menyusui dini (IMD) (p-value=0.004), dukungan suami (p-value=0.007), dan pernikahan dini (p-value=0.012) dengan pemberian ASI eksklusif. Simpulan: Pengetahuan, pekerjaan,  pelaksanaan inisiasi menyusu dini (IMD), dukungan suami, dan pernikahan dini berhubungan dengan pemberian ASI eksklusif. Saran: Diharapkan bidan dapat membantu ibu menyusui tentang dampak jika menikah usia dini, pentingnya pemberian ASI dan informasi tentang pentingnya dukungan suami pada ibu, sehingga suami mengerti dan mengetahuinya melalui penyuluhan dan konseling serta menggunakan iklan atau poster.   Kata Kunci: Dukungan Suami; Pekerjaan; Pelaksanaan Inisiasi Menyusu Dini (IMD);  Pemberian ASI Eksklusif;  Pengetahuan; Pernikahan Dini.